Research on the cultivation of green competitiveness among chinese heavily polluting enterprises under country/district environmental regulations - Zhang, Tongjian; Zho, Jian-ya; Hussain, Rana Yassir; Wang, Min; Ren, Kai (Frontiers in Environmental Science, 2022)
Abstract: In the course of China's economic development, ecological problems have become increasingly serious. Green technology innovation is an important driving force for the simultaneous development of China's economy and ecology. Among them, the cultivation of green technology innovation for heavily polluting enterprises is a top priority. "Porter Hypothesis" pointed out that environmental regulation can drive the growth of green technology innovation in enterprises, but it is still in an unknown state in China's heavily polluting enterprises. County environmental regulation is the hub of China's environmental regulation. This research used the structural equation model to examine the existence and effectiveness of the "Porter Hypothesis" by taking samples of heavily polluting enterprises in China's counties and districts and revealing the mechanism by which environmental regulation promotes green technology innovation, and proposed specific improvement strategies for environmental regulation, thereby enhancing the green competitiveness of heavily polluting enterprises. The findings demonstrate that the county government of our country needs to optimize the incentive-type environmental regulations to drive the green process innovation of enterprises and to optimize the voluntary environmental regulations to drive the green process innovation and the "three wastes" treatment innovation. At the same time, increase the driving force of "three wastes" treatment innovation on the green competitiveness of enterprises.